Designing ESP materials from social semiotic perspective: A design-based approach - Hikmah Pravitasari; Nurhadianty Rahayu (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2021)
This research aims at developing Supplementary English Material to fulfil the students needs toward the material at midwifery academy using Project-based Learning (PBL). This research uses Design Based Research (DBR). It is conducted in four steps, i.e. analysis of the practical problem, product development, try out of the product development and reflection. The findings show that the existing English materials contain general English material and it is less specific to be used for the students of midwifery study program. The supplementary project book contains theoretical theories of ESP and PBL. The prototype is validated and reviewed by two experts in English Language Teaching (ELT) and expert of Midwifery. To get the feasible product, the prototype was tried to be implemented three times in the classroom. Through observation, questionnaire, and focus group discussion that involved the researcher, the instructor, and students, the draft is finalized. Therefore, after going through the stages, it could be said that the draft is feasible to be applied as supplementary material to teach students of midwifery study program. It is expected that the module can give some contribution and improvement for English teaching and learning.